Photoelectrochemical activity of CuO-CdS heterostructured catalyst for CO2 reduction - Tarek, Mostafa; Karim, Kaykobad Md Rezaul; Sumaya, Sarmin; Ong, Huei Ruey; Hamidah, Abdullah; Cheng, Chin Kui; Khan, Maksudur Rahman (Institute of Physics Publishing, 2020)
The present study explored the efficiency of a p-n heterostructured hybrid catalyst CuO-CdS to convert CO2 selectively into methanol by photoelectrochemical (PEC) method under concurrent visible light irradiation and a bias potential -0.4 V vs. NHE. The results showed that the inclusion of CdS with CuO significantly enhanced the activity of PEC CO2 reduction to produce methanol by facilitating the separation of photogenerated electron-hole (e-/h+) pairs through the p-n heterostructured architectures. The yield of methanol, the incident photon current efficiency (IPCE) and quantum efficiency (QE) in PEC CO2 reduction were achieved 35.65 μmoleL-1cm-2, 20.24% and 24.11%, respectively. The present work bears a new understanding into the fabrication of high-performable artificial p-n type heterostructured catalyst which is capable to function as a catalyst for photocathode for the reduction of CO2 and remarkable improvement in methanol yield under visible light illumination.